BAGJA appreciative inquiry-based student worksheet as an innovative learning tool to improve creative thinking - Nurdiana, Ani; Caswita, Caswita; Noer, Sri Hastuti (Indonesian Journal of Science and Mathematics Education, 2025)
This study successfully developed a BAGJA appreciative inquiry-based student worksheet that effectively improves students' creative thinking skills in mathematics, especially trigonometry. This study aims to produce teaching media in the form of student worksheet based on the BAGJA appreciative inquiry model to improve students' creative thinking skills. The results showed that the BAGJA appreciative inquiry-based student worksheet was categorized as valid, scoring 0.72 from material experts and 0.66 from media experts. The practicality score reached 0.81 from students and 0.96 from teachers, which stated that this product was practical. The effectiveness test showed a sig=0.00<α=0.05, which means this product effectively improves students' creative thinking skills. The BAGJA appreciative inquiry approach applied in this student worksheet has stimulated students to think more creatively, analytically, and innovatively when solving math problems. The implications of this research include improving the quality of learning by encouraging the development of innovative teaching materials and opening up opportunities for further research in applying similar approaches to other materials to improve students' creative thinking skills more broadly.